A V2O5-based freestanding anode with high rate and superior cycle life for potassium storage. (June 2022) - Jiang, Xiang; Tian, Shuang; Jiang, Qinting; Xu, Chengrong; Gao, Peibo; Zhou, Tong; Zhou, Jin
Abstract: Potassium-ion batteries (PIBs) are emerging as a new hotspot of research in energy storage technology due to the resource abundance and low cost of potassium. However, the large size of K + results in a significant challenge for developing high-rate and long-life anode materials for PIBs. Herein, we proposed a freestanding anode material of carbon-coated V2 O5 nanosheets arranged vertically on carbon fibers (C@V2 O5 @CNFs) for potassium storage. The CNFs as the skeleton regulates the vertical alignment of V2 O5 nanosheets, thereby avoiding the self-agglomeration effectively. Moreover, the carbon coating layer not only stabilizes the structural integrity and further enhances the electrical conductivity of hybrid electrodes. Consequently, the C@V2 O5 @CNFs shows excellent reversible capacity and long-term cycle stability. Graphical abstract: Image 1 Highlights: A V2 O5 -based freestanding anode for PIBs was fabricated. The carbon fibers relieve the aggregation of V2 O5 nanosheets. The carbon coating improves the integrity and conductivity of the electrode. The C@V2 O5 @CNFs shows excellent cycling performances up to 5000 cycles.